RANCANG BANGUN SISTEM INFORMASI E-LEARNING PADA SMK NEGERI 3 BATAM - Anjelita, Poppy; Rosiska, Evan (LPPM Universitas Putera Batam, 2019)
The development of technology in the era of globalization attracted many people in finding alternatives to solve problems in the field of information technology. The progress of information technology is an interest for humans to support and facilitate their work. One way is to use technology to get information, which is in the field of education. SMK Negeri 3 Batam is a vocational high school in the field of technology and engineering. Vocational school located in Batam precisely located at JL. Letjend S.Parman, Kelurahan Duriangkang, Sungai Beduk Subdistrict, which was established precisely in 2007. In accessing information in the form of announcements, currently SMK Negeri 3 still uses bulletin media in information distribution and through microphones in the form of notifications to students, this is not all students listen to the announcement carefully and the information becomes less clear which will make students not know the information. Thus need a learning system that can solve this, one of which is a learning system or by using internet-based technology that will make it easy for students to access information related to learning material and access to information in the form of announcements. E-learning is the use of electronic technology to create learning experiences. The e-learning system can be implemented through technology support directed to support the teaching process that is packed with electronic / digital format and in its implementation requires a website-based computer media on an internet site.